Extensive Variation in the O-Antigen Gene Cluster within One Salmonella enterica Serogroup Reveals an Unexpected Complex History - Wang, Lei (American Society for Microbiology, 2002)
The 46 serogroups of Salmonella enterica have different O-antigens, and each is thought to have a specific form of the O-antigen cluster. Comparison of the 145 serovars of serogroup B revealed much more intraserogroup genetic diversity than expected. The O27 factor, due to an α 1-6 linkage between O units in place of the more common α 1-2 linkage and previously thought to be due to a converting bacteriophage, is now shown to be due to a wzy(α(1-6)) gene located within the major gene cluster. Surprisingly a remnant of this gene in all O27(−) serovars shows that the ancestor was O27(+). There are six distinct gene cluster forms, five apparently derived by a series of deletions and one by an insertion from an ancestral O27(+) form present in 57 serovars. The history of the gene cluster and movement between subspecies I and II can be traced. Two of the derivative forms still have a functional wzy(α(1-6)) gene, while in three it has been inactivated by deletion or insertion. Two of the forms lacking a functional wzy(α(1-6)) gene have the wzy(α(1-2)) gene first described for strain LT2 as rfc, whereas for the third the wzy gene has not been located.